OPTIMALISASI TANAH KRITIS DENGAN MIKORIZA DAN FOSFAT UNTUK PENINGKATAN PERTUMBUHAN DAN SERAPAN HARA KEDELAI - Yusrizal Yusrizal; Muyassir Muyassir; Syafruddin Syafruddin (Jurnal Agrotek Lestari, 2018)
This study aims to identify the effects of mycorrhiza arbuscular and phosphate source fertilizer on the growth and nutrients absorption of soybean on critical land. The research was carried out in the experimental garden of Agricultural Faculty, University of Syiah Kuala Darussalam, Banda Aceh. The research was done in an experiments using polybag of random design group (shelves) consisting 2 factors, namely mycorrhiza arbuscular consisting of 4 standards without mycorrhiza, glomus 10 g, mycorrhiza gigaspora 10 g, and mixture glomus 5 g + gigaspora 5 g and phosphate fertilizer consisting 4 factors namely without phosphate fertilizer, rock fosfat, guano, and SP-36. The result showed that the interaction effect of mycorrhiza glomus and guano phosphate application improved growth and nutrients absorption of soybean plants. Key words: Gigaspora, Glomus, guano, rock phosphate, soybean, SP-36/>